Miniature electroparticle-cuff for wireless peripheral neuromodulation. (21st May 2019) - Hernandez-Reynoso, Ana G; Nandam, Shrenevas; O'Brien, Jonathan M; Kanneganti, Aswini; Cogan, Stuart F; Freeman, Daniel K; Romero-Ortega, Mario I
Abstract: Objective . Recent developments in peripheral nerve electrodes allow the efficient and selective neuromodulation of somatic and autonomic nerves, which has proven beneficial in specific bioelectronic medical applications. However, current most clinical devices are wired and powered by implantable batteries which suffer from several limitations. We recently developed a sub-millimeter inductively powered neural stimulator (electroparticle; EP), and in this study, we report the integration of the EP onto commercial cuff electrodes (EP-C) allowing the wireless activation of peripheral nerves. Approach . The current output of this device was defined at different magnetic field strenghts, and with respect to external antenna distance and activation angles. In acute in vivo testing, stimulation of the rat sciatic nerve (ScN) with the EP-C was able to evoke motor responses quantified by 3D tracking of the hind limb movement. Motor recruitment curves were obtained in response to variations in magnetic field strength (0–92.91 A m −1 ), stimulation frequencies (2–7 Hz), and pulse widths (50–200 µ s). Main results . The results show constant output voltage throughout 50 400 stimulating cycles on a benchtop setting, and successful ScN motor activation with a 4 cm distance between external antenna and receiver. We achieved optimal motor recruitment indicated by maximizing range of hindlimb movement (6.01  ±  2.92 mm) with a magnetic field of 40.02  ±  2.85 A m −1 and 150 µ s pulse width. Stimulating pulse width or frequency did not significantly influence motor recruitment. Significance . We confirmed that continuous stimulation for 14 min using monophasic pulses did not deleteriously affect the evoked motor responses when compared to wired charge-balanced biphasic electrical stimulation. We observed, however, a 36%–44% decrease in the evoked limb movement in both groups over time due to muscle fatigue. This study shows that the EP-C device can be used effectively for peripheral nerve neuromodulation.